The Education of School Counsellors in Canada - Bedal, Carl L. (Canadian Journal of Counselling and Psychotherapy, 2012)
The author differentiates between counsellor education and the education of school counsellors. He uses a 1978 study of school guidance services in Canada in which provincial guidance directors were interviewed to gain their perceptions of various guidance-related issues. The study indicated that departments of education prefer the term "guidance" to "counselling" and the terminology affects how guidance is practised in the schools and how school counsellors are trained. The study identified several discrepancies between the training given to and practice expected of school counsellors. It also found that national priorities were considered important neither to the training of counsellors nor to the practice of guidance in the schools. Unexpectedly, the study found that the responsibility for in-service training of school counsellors was seldom assumed by the training institutions.